Innovative therapeutic strategy for B-cell malignancies that combines obinutuzumab and cytokine-induced killer cells. Issue 7 (16th July 2021) - Dalla Pietà, Anna; Cappuzzello, Elisa; Palmerini, Pierangela; Ventura, Annavera; Visentin, Andrea; Astori, Giuseppe; Chieregato, Katia; Mozzo, Valentina; Perbellini, Omar; Tisi, Maria Chiara; Trentin, Livio; Visco, Carlo; et al.
Abstract : Background: Patients affected by aggressive B-cell malignancies who are resistant to primary or salvage chemoimmunotherapy have an extremely poor prognosis and limited therapeutic options. Promising therapeutic success has been achieved with the infusion of CD19 chimeric antigen receptor-T cells, but several limits still restrain the administration to a limited proportion of patients. This unmet clinical need might be fulfilled by an adoptive immunotherapy approach that combines cytokine-induced killer (CIK) cells and monoclonal antibodies (mAb) to the CD20 antigen. Indeed, CIK cells are an effector population endowed with antitumor activity, which can be further improved and antigen-specifically redirected by clinical-grade mAb triggering antibody-dependent cell-mediated cytotoxicity. Methods: CIK cells were generated from peripheral blood of patients affected by different B-cell malignancies using a blinatumomab-based cell culture protocol. Effector cells were combined with the anti-CD20 mAb obinutuzumab and their therapeutic activity was assessed both in vitro and in vivo. Results: CIK cells were successfully expanded in clinically relevant numbers, starting from small volumes of peripheral blood with extremely low CD3 + counts and high tumor burden. This relied on the addition of blinatumumab in culture, which leads to the simultaneous expansion of effector cells and the complete elimination of the neoplastic component. Moreover, CIK cells were highly cytotoxic in vitro against both B-cell tumor cell lines and autologous neoplastic targets, and had a significant therapeutic efficacy against a B-cell malignancy patient-derived xenograft on in vivo transfer. Conclusions: The combination of an easily expandable CIK cell effector population with a mAb already in clinical use establishes a tumor antigen-specific redirection strategy that can be rapidly translated into clinical practice, providing an effective therapeutic alternative for B-cell malignancies without any need for genetic modifications. Additionally, the approach can be potentially applied to an extremely vast array of different tumors by simply substituting the targeting mAb.